1989
DOI: 10.1111/j.1464-410x.1989.tb06053.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Recurrent Bladder Tumours by Transrectal and Abdominal Ultrasound Compared with Cystoscopy

Abstract: Transrectal and transabdominal ultrasound was used to detect the recurrence of bladder tumours and compared with conventional cystoscopy. Forty patients with a previous history of bladder tumour were examined by these methods; 50% had a recurrence. Transabdominal and transrectal ultrasound together identified 95% of recurrences; 1 tumour (diameter 1 mm) was missed. The false positive rate was 5% and these areas, identified wrongly by ultrasound as tumour, were shown to be scars on cystoscopy. Combination ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
3

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 9 publications
1
8
0
3
Order By: Relevance
“…In addition, both false-positive and -negative results occurred on sonography and were due to the following: (1) the characteristics of FBWAs, including lesions smaller than 5 mm and those with a flat or infiltrating gross appearance, which were difficult to detect, as reported in previous studies [3][4][5][6] ; (2) projections; and (3) technical factors, including overweight habitus, an obvious obstacle to sonography, and, despite the prospective nature of the study, a limited number of patients in whom optimal bladder filling was not fully achieved. Adherent clots, well-known causes of false-positive sonographic findings, 3 did not pose a diagnostic dilemma in this study.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In addition, both false-positive and -negative results occurred on sonography and were due to the following: (1) the characteristics of FBWAs, including lesions smaller than 5 mm and those with a flat or infiltrating gross appearance, which were difficult to detect, as reported in previous studies [3][4][5][6] ; (2) projections; and (3) technical factors, including overweight habitus, an obvious obstacle to sonography, and, despite the prospective nature of the study, a limited number of patients in whom optimal bladder filling was not fully achieved. Adherent clots, well-known causes of false-positive sonographic findings, 3 did not pose a diagnostic dilemma in this study.…”
Section: Discussionmentioning
confidence: 89%
“…[3][4][5][6][7][8] However, most of these studies were retrospective, sometimes conducted in small cohorts of patients, and all were carried out with old sonography equipment. Nowadays, new modes for acquiring sonographic images such as tissue harmonic imaging (THI) and spatial compound imaging (SCI) are widely available and have improved diagnostic performance for sonographic examinations in a variety of abdominopelvic pathologic conditions.…”
mentioning
confidence: 99%
“…Results using transabdominal ultrasound have given tu mour detection rates of 50, 74 and 77% in the studies performed by Malone et al [3], Vallancien et al [5] and Juul et al [2], respectively. Davies et al [6] have shown a 95% detection rate of recurrent tumours when transab dominal and transrectal ultrasound were used in combina tion in anaesthetised patients at the time of cystoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Accuracy with cytology ranges from 72 to 98% [4,9,10], the lower figure of cytological detection reflects the fact that only one specimen was taken. It has been shown that optimum detection rates of tumour are found when at least three separate urine samples are taken [11-Itzchaky et al [7] Brun et al [8] Malone et al [3] Vallancien et al [5] Juul et al [2] Davies et al [6] 37 62 TA 95 68 TA 126 50 TA 100 74 TA 186 77 TA 80 40 TA 85 TR 95 TA + TR This study 125 82 TA 77 TR 90 TA + TR 13].…”
Section: Introductionmentioning
confidence: 99%
“…Otros estudios han comparado el diagnóstico histológico tras la RTU con las piezas de la cistectomía 2 . Existen estudios que comparan la cistoscopia con técnicas de imagen combinadas como por ejemplo la ecografía abdominal y la transrectal con el fin de reducir el número de cistoscopias 3,4 . Un estudio reciente propone la fulguración endoscópica ambulatoriamente en el seguimiento de las recidivas de los tumores vesicales de bajo grado y estadio, no considerando esencial la biopsia y por consiguiente el diagnóstico histológico en este grupo de tumores 5,6 .…”
Section: Discussionunclassified